2000
DOI: 10.1016/s0012-821x(00)00178-3
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the Messinian APTS from sedimentary cycle patterns in the lacustrine Lava section (Servia Basin, NW Greece)

Abstract: A high-resolution cyclostratigraphy and magnetostratigraphy is presented for the Messinian lacustrine Lava section from the Servia Basin in NW Greece, constraining more precisely the absolute ages of magnetic polarity subchrons C3An.1n and C3An.2n. The section contains 15 distinct sedimentary cycles of alternating dark-and light-coloured marls, while the gamma-ray attenuation record reveals an additional five to six cycles. The cycles in the lower half of the section are on average 5.3 m thick, as opposed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 21 publications
1
26
0
5
Order By: Relevance
“…1), which suggest that the dip-slip motion was preceded by a strike-slip activity. Lacustrine sediments of about 5 Ma old (Steenbrink et al 2000) in the footwall of the Aliakmon Fault show no evidence for synsedimentary SE-ward tilting, but at present have a SE tilt. This provides a maximum age for significant dip-slip activity of the Aliakmon fault zone of $5 Ma.…”
Section: Transverse Structures and Late Neogene Extensional Basinsmentioning
confidence: 71%
“…1), which suggest that the dip-slip motion was preceded by a strike-slip activity. Lacustrine sediments of about 5 Ma old (Steenbrink et al 2000) in the footwall of the Aliakmon Fault show no evidence for synsedimentary SE-ward tilting, but at present have a SE tilt. This provides a maximum age for significant dip-slip activity of the Aliakmon fault zone of $5 Ma.…”
Section: Transverse Structures and Late Neogene Extensional Basinsmentioning
confidence: 71%
“…The investigations on marine cores covering the last climatic cycle off the Saharan coast has clearly demonstrated that during GCS glacial MIS it is dry in NW Africa (Hooghiemstra, 1989;Hooghiemstra et al, 2006). Ptolemais diagrams (Greece) show that cooler or drier periods were cyclically present very early on and well before the period considered here (Steenbrink et al, 2000(Steenbrink et al, , 2003.…”
Section: The Extent Of the Cold Or Dry Climates During Gcs Glaciationsmentioning
confidence: 79%
“…When going further back in time, complex vegetation successions have also been observed, such as in the site of Ptolemais (Greece) (Fig. 1) during the Early Pliocene (Steenbrink et al, 2003) and at an earlier time in the Messinian, but less clearly (Steenbrink et al, 2000).…”
Section: Steps Of Vegetation Successionsmentioning
confidence: 98%
“…Cenozoic lake basins in the Aegean region (e.g., Van Vugt et al, 1998Steenbrink et al, 1999Steenbrink et al, , 2000. In the absence of age control, taking account of the regional context Westaway et al (2004) inferred that its deposition ended around ∼3 Ma, being followed by a switch to fluvial incision accompanying a regional increase in uplift rates.…”
Section: Introductionmentioning
confidence: 99%